2018
DOI: 10.3126/jonmc.v6i2.19566
|View full text |Cite
|
Sign up to set email alerts
|

Age Distribution of Patients Presenting With Typhoid and Paratyphoid Fever in Kathmandu, Nepal

Abstract: Background: Enteric fever is a significant cause of morbidity in Nepal. In the past, Salmonella entericaserovar Typhi (S. Typhi) was the major causative organism of enteric fever. However, more recently, Salmonella entericaserovar Paratyphi (S.Paratyphi) A has been isolated from most patients presenting with enteric fever in various regions of Nepal. This study aimed to evaluate age differences in patients presenting with typhoid and paratyphoid fever.Materials & Methods: Between December 2014 and October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…34 In this study, it was found that majority of typhoid fever cases accounted to the age-group of 11 to 30 years as revealed by various other studies from Nepal. [35][36][37][38] Even though more than half of the blood cultures were obtained from patients >30 years of age, S. Typhi was not found to be culture positive from this age-group. Persons of age group 15 to 30 are often engaged in outdoor activities and are more inclined to consumption of foods from street or local vendors which can significantly contribute to higher incidence of typhoid fever.…”
Section: Discussionmentioning
confidence: 99%
“…34 In this study, it was found that majority of typhoid fever cases accounted to the age-group of 11 to 30 years as revealed by various other studies from Nepal. [35][36][37][38] Even though more than half of the blood cultures were obtained from patients >30 years of age, S. Typhi was not found to be culture positive from this age-group. Persons of age group 15 to 30 are often engaged in outdoor activities and are more inclined to consumption of foods from street or local vendors which can significantly contribute to higher incidence of typhoid fever.…”
Section: Discussionmentioning
confidence: 99%